Avaliação da resistência à corrosão e das propriedades mecânicas da junta soldada de aço inoxidável duplex - Higa, Silvia Midori (Universidade Federal de São Carlos, 2015)
The corrosion resistance and mechanical properties of hardness and toughness of a welded joint multipass duplex stainless steel have been evaluated under the condition with post-weld heat treatment and as-welded. The microstructure along the weld varied as a function of the thermal cycles of the welding process. The heat affected zone (HAZ) showed a higher amount of ferrite and larger grain size. The weld metal (WM) showed more refined microstructure, given by the metal composition of addition used. The parent metal (PM) has not microstructural changes to be far to the fusion zone. The results obtained in electrochemical tests, immersion and mechanical showed that the HAZ presented the pitting potential less noble and higher degree of sensitization in relation to WM and PM. The higher hardness and lower toughness were observed in WM due to the refined microstructure. It was also observed that the post-weld heat treatment reduced the hardness and increased toughness over the joint, reducing the difference of values of these mechanical properties between different regions of the weld. In the corrosion resistance, the effect of the heat treatment was observed in the reduction of the degree of sensitization of the HAZ, it is not significant in pitting potential. The highest rate of corrosion in the welded joint was obtained in the condition as-welded, and observed an attack in the HAZ region. Considering the degree of sensitization and the rate of corrosion of the HAZ, we investigated the presence of precipitates in the region by means of scanning electron microscopy (SEM) and transmission (TEM) with a qualitative chemical analysis and semi-quantitative for energy dispersive X - ray (EDS). The results showed the presence of chi phase, sigma and secondary austenite responsible for the sensitization of the joint as-welded.
Evaluation of the corrosion resistance and the mechanical properties in duplex stainless steel joint
Keywords: Corrosão localizada; Duplex; Tenacidade; Dureza; Solda; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS